Detection of nickel and palladium contact hypersensitivity by a flow cytometric lymphocyte proliferation test. Issue 3 (22nd December 2014) - Spoerri, I.; Scherer, K.; Michel, S.; Link, S.; Bircher, A. J.; Heijnen, I. A. F. M.
Abstract We established a flow cytometric lymphocyte proliferation test (LPT) for the detection of nickel (Ni) and palladium (Pd) sensitization. Eighty‐one consecutive patients with an indication for patch test (PT) were tested by LPT with Ni (NiSO4) and Pd (Na2PdCl4 and PdCl2) salts. The imprecision of the LPT was low (coefficient of variation 7.2%). Using PT as a diagnostic reference, the sensitivity and specificity of LPT were 74.4% and 80% for NiSO4, 74.4% and 78.3% for Na2PdCl4, and 57.2% and 85.4% for PdCl2, respectively. For both Ni and Pd, the likelihood ratio for a positive PT markedly increased with increasing LPT value. With medical history as a reference, the sensitivity and specificity were 40.6% and 82.1% for LPT and 59.4% and 89.7% for PT, respectively. Combination of LPT and PT resulted in a higher specificity of 95%, albeit lower sensitivity of 34.4%. In conclusion, flow cytometric LPT represents a reliable and useful method for the detection of Ni and Pd sensitization. LPT values correlate with PT results and, when used in combination with PT, increase test specificity.